New insights in the heterogeneous photocatalytic removal of U(VI) in aqueous solution in the presence of 2-propanol - Salomone, Vanesa Natalia (2015)
The efficiency of heterogeneous photocatalysis with TiO2 under UV light (HP) for the removal of uranyl ion from water (0.25mM, pH 3) in the presence of 2-propanol (2-PrOH) was evaluated. The effects of the counterion of the uranyl salt or anions present in the system and the use of quartz and glass photoreactors were analyzed. High U(VI) removal efficiencies were obtained, reaching 100% when starting from uranyl nitrate and 1M 2-PrOH after 60min in a quartz photoreactor. The reaction in the absence of 2-PrOH was rather low, reaching around 50% in 120min under the same conditions. The photocatalytic reaction yield was similar when the reaction started from uranyl perchlorate, but systems where acetate was present showed less removal, both in the absence and the presence of 2-PrOH. Yields with the quartz photoreactor were always higher than those with the glass reactor.Kinetic and mechanistic analyses were performed. Comparisons with the photochemical systems in the absence of TiO2 were made. The results indicated that the uranyl nitrate system in the presence of 2-PrOH gave similar results with and without TiO2, but the other systems gave higher removal yields when TiO2 was used. The proposed mechanism suggests that U(VI)/U(V) reduction is mediated by conduction band electrons and not by reducing organic radicals, a distinctive feature of the system. For all studied conditions, the photocatalytic treatment allowed a better recovering of the precipitated uranium.